아동의 발달지연과 가족환경과의 관련성 - 이성아(Seong-A Lee); 박수현(Su-Hyun Park) (한국콘텐츠학회 논문지, 10(11), 2010)
The purpose of this study is to investigate the relationship between family environment and developmental delay in a sample of normal 3-5 years old children. Developmental evaluation is performed using K-DDST II and K-ASQ. Family environment is researched by survey. The survey questions include children's order, family numbers, religion, patient's age, patient's education history. Subject is selected between the age of 3-5 years old children. The test has been conducted to find an interrelationship between a developmental delayed result and family environment. Study has found that there is a strong relationship between developmental delay and children's family environment. Family environment factor includes children's gender, birth order, parent's age, education history. Therefore, developmental evaluation must have consideration on the element of children's family environment for developmental delay test because of a strong relationship between family environment and developmental delay result. 본 연구는 3-5세 아동을 대상으로 발달선별검사인 K-DDSTII, K-ASQ을 실시하여 발달지연 결과를 가진 하부검사와 가정환경 간의 관련성을 알아보았다. 연구결과, K-DDST에서는 가족환경 중 아버지의 나이와 개인사회성, 어머니의 나이와 교육력이 대동작과 통계적으로 차이가 있었다. 또한 K-ASQ에서는 의사소통과 성별, 출생순서와 부모의 교육력에서 통계적으로 유의한 차이가 있었으며, 문제해결과 출생순서, 그리고 하부검사 중 하나이상의 발달지연이 있는 경우는 성별과 출생순서와 유의미한 통계적 차이가 있었다. 본 연구결과 발달선별 검사 시에 가족환경에 관한 조사가 병행된다면 아동 발달에 대한 선별검사의 효율성을 높이는 방안의 하나일 수 있음을 제시 할 수 있을 것이다.